Rotational Isomerism, Electronic Structures, and Basicity Properties of "fully-Reduced" V14-type Heteropolyoxovanadates - Kondinski, Aleksandar; Heine, Thomas; Monakhov, Kirill Yu (Inorganic Chemistry, 2016)
We investigated computationally the α-, γ-, and β-isomeric structures, relative stabilities, and the electronic and basicity properties of magnetic [VIV14E8O50]12- (hereafter referred to as V14E8) heteropolyoxovanadates (heteroPOVs) and their heavier chalcogenide-substituted [VIV14E8O42X8]12- (V14E8X8) derivatives for E = SiIV, GeIV, and SnIV and X = S, Se, and Te. We used density functional theory (DFT) with scalar relativistic corrections in combination with the conductor-like screening model of solvation. The main purpose of this investigation is to introduce the structure-property relations in heteroPOVs as well as to assist the synthesis and molecular deposition of these molecular vanadium-oxide spin clusters on surfaces. "Fully-reduced" polyoxoanions V14E8 and V14E8X8 are virtually comprised of [VIV14O38]20- V14 skeletons of different symmetries, that is, D2d for α-, D2 for γ-, and D4h for β-isomers, which are stabilized by the four E2O32+ and four E2OX22+ moieties, respectively. Our DFT calculations reveal stability trends α > γ > β for polyoxoanions V14E8 and V14E8X8, based on relative energies and HOMO-LUMO energy gaps. The α-isomeric polyoxoanions V14E8 and V14E8X8 with the high negative net charges may easily pick up protons at the terminal E-Ot and E-Xt sites, respectively, which is evidenced by strongly negative enthalpies of monoprotonation. Energetically favorable sites on polyoxoanions α-V14E8 and α-V14E8X8 for electrostatic pairing with countercations were also determined. Among β and γ isomers, the hitherto unknown γ-[V14Sn8O50]12- and γ-[V14Sn8O42S8]12- seem to be the most viable targets for isolation. Furthermore, these Sn-substituted polyoxoanions are of high interest for electrochemical studies because of their capability to act as two-electron redox catalysts.
CRIS-Team Scopus Importer:2023-03-20